Turning time estimation model for region coverage - Doan, V K; Lim, M H; Ong, Y S; Jung Soon Jang; Vavrina, M A; Vian, J L; Barhorst, J (2010 International Conference on Computational Problem-Solving, 2010)
In region coverage, UAVs typically follow a certain pattern of combing through a region. In this paper, we present a turning time model for estimating the time cost for UAV. Based on this, we explore two strategies of scanning as a basis for a memetic computing search: the raster and circular scanning strategies. To our knowledge, there has been no attempt to quantitatively model the turning time cost for UAV scanning. The objective is to ultimately achieve polygon decomposition as a form of task division between UAVs using a memetic computing approach. Some results of simulation and validation based on known UAV dynamics are presented.